Pengaruh Agresivitas Pajak dan Kepemilikan Manajerial Terhadap Corporate Social Responsibility dalam Mewujudkan Sustainable Development Goals - Eko Purwanto; Antonius Bimo Rentor; Mega Nuraini Hadi (Universitas Kristen Maranatha, 2022)
Since the urgent demand of SDGs entails Indonesian development agenda, it is essential forcompanies to proactively concern the thematic issues of human, nature, and technologyharmonization and stability. To achieve this goal, this study aims to provide a portrait ofvariables affecting the Corporate Social Responsibility (CSR) discovery in pharmaceuticalcompanies listed on Indonesia Stock Exchange (IDX) from 2016 to 2020 in realizingSustainable Development Goals (SDGs). For this purpose, CSR discovery is the dependentvariable while tax aggressiveness and managerial ownership are the independent factors. Thepharmaceutical companies that listed in IDX between 2016 and 2020 make up the population.Thus, the secondary data for this study is the financial reports of 10 pharmaceutical firms thatwere obtained from the official IDX website using the purposive sampling method. To assessthe data, classic assumption test, multiple linear regression coefficient test, determination test,correlation test and hypothesis testing were used. Results showed that tax aggressiveness andmanagerial ownership both influence CSR discovery. To sum up, tax aggressiveness andmanagerial ownership in the IDX-listed pharmaceutical companies in the 2016-2020 periodhave an impact on CSR discovery.Keywords: Tax Aggressiveness, Managerial Ownership, Corporate Social Responsibility(CSR)